He kupenga mate pukupuku uu mo ngā wāhine Māori : Te Whare Tapa Whā : a multidimensional exploration of the impacts of breast cancer among wāhine Māori survivors : a thesis presented in partial fulfilment of the requirements for a Master of Philosophy in Māori Studies at Massey University, Palmerston North, New Zealand - Ripia, Lucy Margareth (Massey University, 2013)
Verse 1: Breast Cancer The illness that threatens the lives of mothers, daughters, sisters and wives Why me, we ask, oh why me? Perhaps the answer lies deep within the family A breast cancer diagnosis for wahine Maori (Maori women) impacts on the whole whanau (extended family), hapu (sub-tribe) and iwi (tribe). This thesis captures the experiences of seven wahine Maori who went through the diagnosis of, and treatment for, breas t cancer. A personal experience of breast cancer provided the impetus for choosing this topic, enriched by the opportunity to speak with other women and reflect on their own experiences. The qualitative method of interviewing and sharing experiences betwee n the researcher and the participants was exceptionally enlightening for all concerned. This reciprocity and exchanging of experiences produced similar as well as unique, individual stories. Surrounding the design, data gathering and analysis were kaupapa Maori (customs, traditions and philosophies of being Maori) concepts and research methods to help ensure the cultural safety of all participants, as well as garner a deeper understanding of the information gathered from a Maori perspective. Whakapapa (genealogy) played a significant role in all the interviews. For various reasons, tupuna (ancestors) remained a source of strength as well as a source of vulnerability when it came to acknowledging their contribution to the wellness of the participants. The women felt reminded to search for strength from their tupuna to help with their healing, yet were also mindful of the reasons they were diagnosed with breast cancer in the first instance, through whanau history and genetic makeup. This multidimensional exploration of how breast cancer impacts on the well-being of Maori women uses Te Whare Tapa Wha (Durie, 1994) to capture the aspects of well-being in a Maori context. The objective of this research therefore is to investigate the experiences of Maori women who have travelled the journey of breast cancer. Their stories will provide an increased understanding of the impacts on their physical, spiritual and mental and emotional wellness, including the impacts on whanau structures and relationships
Keywords: Breast cancer patients; Psychology; Māori women; Health and hygiene; New Zealand